An Autopsy Case of a Pregnant Woman With Severe Placental and Fetal Damage From Domestic Violence. (September 2015) - Kanawaku, Yoshimasa; Takahashi, Shirushi; Kanetake, Jun; Funayama, Masato
Abstract : Abstract: We present an autopsy case of a pregnant woman who was a victim of domestic violence. The deceased showed injuries mainly to her head and abdomen. Postmortem examination revealed 1400 mL of abdominal hemorrhage, ablation of the perimetrium, placental avulsion, and intracranial hematoma. The cause of death was diagnosed as hemorrhagic shock. The uterus contained a fetus of 7 months' gestational age. Fetal autopsy revealed laceration of the lungs, laceration and avulsion of the liver, and 15 mL of hemoperitoneum. Both placental and fetal injuries suggested repeated severe attacks to the abdomen, such as those expected to result from kicking or hitting.